Additional Food Supplementation Of High Animal Protein Food, Calcium, And Zinc In Children Aged 6-24 Months As An Effort To Increase Children's Body Length - Wiyono, Sugeng; Muntikah, Muntikah; Meilinasari, Meilinasari (Window of Health : Jurnal Kesehatan, 2023)
The 2021 Basic Health Research (Riskesdas) results of the Ministry of Health of the Republic of Indonesia show that stunting prevalence in five-year-old children is 24.4%. Children who are stunted until the age of 5 years will find it challenging to overcome, so it will continue into adulthood and can increase the risk of offspring with low birth weight. Stunting will cause long-term impacts, namely impaired physical, mental, intellectual, and cognitive development. This research method used true experimental design by providing 50,0 g of nuggets daily for six weeks as high supplements in animal protein, calcium, and zinc. The subjects of this research were children aged 6-24 months, the subjects were randomly assigned. The number of samples based on the sample size calculation was 30 children. Bodyweight was measured using a digital scale, and body length/height was measured using a stadiometer and microtoice. Data was processed and analyzed using computerized statistical software. The results showed that before the intervention was given to the treatment subjects, the average height was 79,6 ± 4,8 cm; after the treatment, the average height was 80,01±4,9 cm. Based on the paired t-test results, there was a significant difference in height of 0,41 ± 0,26 cm (p = 0,000). For initial body weight or before being given treatment to the treatment subjects, there was an average body weight of 10,1 ± 1,5 kg, and after being given treatment, the average body weight was 10,3±1,5 kg, there was no difference (p = 0,082) of body weight after being given supplementation. As a suggestion, it is necessary to develop a more varied form of food so that infants and children of all ages can consume high amounts of supplements in animal protein, calcium, and zinc.